An Analysis on Student Learning Style and Academic Achievement of the Second Year Students of English Study Program FKIP University of Riau - Resti, Mujiana Resti; Johar, Raida Johar; ', Hadriana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this descriptive research was to know kind of learning style among the three (visual, auditory and kinesthetic) which prefer to use by the second year students of English Study Program of FKIP-UR and to know the academic achievement of the students. The participants of this research were 32 students of the second year students of English Study Program of FKIP-UR. This research used the VAK Questionnaire test in analyzing the students’ learning style and used the students’ academic achievement in form of GPA in order to know the students achievement in learning process. This finding research found that from the three types of learning style, the visual learning style is most prevalent among the students. Then, most of the good achievers are kinesthetic learner and most of the learners who taken as a sample have the category Good in their academic achievement.Keywords: Learning Style, Academic Achievement, VAK Learning Style